2015
DOI: 10.1111/cge.12630
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive review of BAP1 tumor predisposition syndrome with report of two new cases

Abstract: The BRCA1-associated protein-1 (BAP1) tumor predisposition syndrome (BAP1-TPDS) is a recently identified hereditary cancer syndrome. Germline mutations in this tumor suppressor gene predispose families to the development of various malignancies. The molecular functions of the gene as well as the clinical phenotype of the syndrome are still being clarified. We sought to conduct a comprehensive review of published research into BAP1-TPDS to more thoroughly delineate the clinical implications of germline BAP1 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(224 citation statements)
references
References 92 publications
(259 reference statements)
3
219
0
2
Order By: Relevance
“…The remaining functional allele is inactivated later in life. There is a high risk of developing tumours, including atypical Spitz tumours (ASTs), UM and cutaneous melanoma (CM), epithelioid malignant mesothelioma (MM) and clear cell RCC 14. For these five main tumour types, the earliest age of onset ranges between 16 and 36 years 14.…”
Section: The Bap1 Tumour Predisposition Syndromementioning
confidence: 99%
“…The remaining functional allele is inactivated later in life. There is a high risk of developing tumours, including atypical Spitz tumours (ASTs), UM and cutaneous melanoma (CM), epithelioid malignant mesothelioma (MM) and clear cell RCC 14. For these five main tumour types, the earliest age of onset ranges between 16 and 36 years 14.…”
Section: The Bap1 Tumour Predisposition Syndromementioning
confidence: 99%
“…Investigators have examined BAP1 in families: i) with high incidence of MM [3,7,9,11,14]; ii) referred to genetic or cancer centers for uveal melanoma [9,12,15] or other melanocytic tumors [13,17]; iii) affected by basal cell carcinoma [16]; iv) having a family history suggestive of the BAP1 cancer syndrome [18]. Other families were examined as part of asbestos surveillance program [10].…”
Section: Case D-ii-3) Somatic Mutations In Exonmentioning
confidence: 99%
“…BAP1 regulates cell cycle control, target genes transcription, and DNA damage repair [2]. The germline mutation in the BAP1 gene is associated with a hereditary tumor predisposition syndrome (BAP1-TPDS, OMIM#614327) that occurs in family members with several cancer types: MM, uveal/cutaneous melanoma, renal cell carcinoma, basal cell carcinoma and other cancers [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. As of March 2016, forty-six families with multiple cases of MM have been analyzed for BAP1 germline alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Whole exome sequencing and subsequent validation studies on familial melanoma revealed a role of MITF and POT1 mutations; however, their actual impact on the disease incidence remains to be determined [52][53][54][55][56]. BAP1 germline mutations were initially identified upon the study of uveal melanoma [57] and later turned out to be involved in the development of several other tumor types [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Instances of lung cancer clustering due to high-penetrance mutations are very infrequent; however, the analysis of individual large families revealed potentially relevant genes [50,51].…”
Section: Other Cancer Typesmentioning
confidence: 99%